Outreach focused cansat project - from design, development to data acquisition and display - Yeung, Mun Lok (2017)
A CanSat is a scaled-down version of a real satellite that do not go into orbit but rather, deployed within the Earth’s atmosphere. Its mission can be carried out during its deployment and can range from collection and analysis of environmental data, image capturing of certain area etc. The low cost and simple design of CanSats offer students not only the opportunity to explore space engineering concepts and face challenges to apply what they have learnt into designing a practical application but also to inspire them to consider joining the STEM field.